Kualitas Pelayanan Berbasis Aplikasi Berkas Mlaku Dewe (Bmw) Di Kantor Kecamatan Sukodono Kabupaten Sidoarjo - Fitrianti, Anindita; Arif, M. Si, Dr. Lukman (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
This research was based on the application service usage of Berkas Mlaku Dewe or BMW, theimplementation of this application service had been established by Sub-District Sukodono Office, SidoarjoRegency since 2015. BMW owned by Sukodono Sub-District Office Sidoarjo Regency. Based on thepurpose of this study is to examine the quality of Service Based Application Berkas Mlaku Dewe (BMW)at Sukodono Sub-District office Sidoarjo Regency. This is a descriptive qualitative study using thetechnique of data collection namely, observation, interview, and documentation. The location of thisresearch was conducted at Sukodono Sub-District office Sidoarjo Regency. The focus of this research isbased on five-dimensional theory about service quality by Parasuraman. In this case, there are 5 researchpoints being used, they are: (1) Tangibles; (2) Reliability; (3) Responsiveness; (4) Assurance; (5) Empathy.The study found out that, 1) The tangible point is considered as good enough; 2) The reliability has beenconducted in accordance to the service procedure; 3) The responsiveness has been good; 4) The assurancehas been constantly getting better according to the observation; 5) The empathy also could be concludedas good enough and clear in delivering information.